Determining teacher performance through digital literacy: emotional intelligence and competence - Sari, Desi Permata; Aima, Havids; Elfiswandi, Elfiswandi (Jurnal Konseling dan Pendidikan, 2024)
There are many factors that influence teacher performance through digital literacy, including emotional intelligence and competence. Based on the results of the achievement level values performance through UKG scores in Indonesia, it is proven that the quality of teachers is still not optimal. And it can be seen from the UTBK results that only 6 schools out of 17 schools are included in the National UTBK ranking. Research has a purpose For test and analyze in a way empirical influence direct intelligence emotional and competence to teacher performance. As well as influence No direct intelligence emotional and competence through mediation digital literacy towards teacher performance. Method used approach quantitative as well as use questionnaire . Deep sample study This using random sampling with total 253 people. Partial least squares (PLS) analysis method with application smartPLS. Research result This show teacher performance, intelligence emotional, competence and digital literacy as construct and reliability with coefficient the lowest is 0.6 and Cronbach's alpha is above 0.7. Study This show that intelligence emotional and competence own significant impact to teacher performance. Other research shows that intelligence emotional and skill own impact big on digital literacy  and digital literacy has an impact on school teacher performance. There is influence significant digital literacy in mediation intelligence emotional to teacher performance . In addition , digital literacy influences and significant mediate competence to teacher performance. It is hoped that the results of this research can advance the science of human resource management and good behavior academics nor practical.